2016
DOI: 10.1016/j.ultrasmedbio.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Histotripsy Process: Bubble Cloud–Cancer Cell Interactions in a Tissue-Mimicking Environment

Abstract: Histotripsy is a non-invasive ultrasonic ablation method that uses cavitation to mechanically fractionate tissue into acellular debris. With a sufficient number of pulses, histotripsy can completely fractionate tissue into a liquid-appearing homogenate with no cellular structures. The location, shape, and size of lesion formation closely match those of the cavitation cloud. Previous work has led to the hypothesis that the rapid expansion and collapse of histotripsy bubbles fractionate tissue by inducing large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 43 publications
1
89
0
Order By: Relevance
“…The use of thermal ablation can be limited for tumors involving the renal hilum, as mechanical and thermal trauma can result in urine leaks, bleeding, urothelial strictures, and loss of renal function (24). Histotripsy, based on cavitation, depends on the rapid expansion and collapse of a bubble cloud to disrupt targeted tissue via focused ultrasound in a purely mechanical method of tissue destruction (5). Previous studies with this technology have demonstrated tissue-selective properties, suggesting that large vessels and collecting system structures may be spared, while tumors and normal parenchyma are lysed (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of thermal ablation can be limited for tumors involving the renal hilum, as mechanical and thermal trauma can result in urine leaks, bleeding, urothelial strictures, and loss of renal function (24). Histotripsy, based on cavitation, depends on the rapid expansion and collapse of a bubble cloud to disrupt targeted tissue via focused ultrasound in a purely mechanical method of tissue destruction (5). Previous studies with this technology have demonstrated tissue-selective properties, suggesting that large vessels and collecting system structures may be spared, while tumors and normal parenchyma are lysed (6,7).…”
mentioning
confidence: 99%
“…RAST is an emerging ablation technology based on histotripsy: a noninvasive and nonthermal focused ultrasound technique that uses short-duration (<20 μs), low-duty-cycle (<1%) ultrasound pulses at high peak negative pressures (>10 MPa). The result is mechanical tissue disruption at the cellular level (5,9). Microbubbles produced by cavitation are visible with conventional B-mode ultrasound in real time throughout the treatment (10,11).…”
mentioning
confidence: 99%
“…The dynamics of a single isolated, spherical, gas-filled bubble in both water and in homogeneous viscoelastic media (representative of the agarose gels) are numerically simulated using an approach similar to previous studies of histotripsy cavitation [25,26,[46][47][48]. In the present study, only acoustically nucleated bubbles are modeled.…”
Section: B Theoretical Modelingmentioning
confidence: 99%
“…A more detailed exploration of the simulation parameter space in relation to the present work will be presented in a future study. Two sets of simulations are carried out using the specified material properties: one where the gel viscosity is taken to be equal to that of water's [25,47,51], μ w , and another where it is taken to be the prescribed viscosity for agarose, μ a (Table II). With the material properties specified, we then calibrate the bubble's unknown initial size by comparing with the experimental data.…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation